The 2nd International Conference on Computational Engineering and Intelligent Systems - Recioui, Abdelmadjid; Bentarzi, Hamid; Dekhandji, Fatma (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Proceedings reprint comprises a collection of the papers presented at the second International Conference on Computational Engineering and Intelligent Systems, held online in the period 18-20 November 2022. The conference focused on computational engineering including modeling, simulation, analysis, and intelligent systems driven by computing and artificial intelligence. The papers included in this collection deal with a range of topics including smart grids, renewable energies, intelligent safety and control systems, power quality and cloud computing.